Income Smoothing in Indonesian State Owned Enterprises - Ramadhanti, Wita (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
This research is intended to know whether Indonesian State Owned Enterprises (BUMN or Badan Usaha Milik Negara) having income smoothing pattern. This study also testing the determinant factors for income smoothing behavior. Positive Accounting Theory is used with its three hypothesis: bonus plan, debt covenant, and political cost. The samples are BUMN that listed in Indonesian Stock Exchange in 2018 which issued completed audited financial statements from 2010-2018. Data then analyzed using logistic regression. The results shows that stock values, bond values, and company size have positive effect on income smoothing practice. The results is consistent with Positive Accounting Theory’s hypothesis of bonus plan, debt covenant, and political costs hypothesis.